Complementation of Yeast Genes with Human Genes as an Experimental Platform for Functional Testing of Human Genetic Variants. Issue 3 (9th September 2015) - Hamza, Akil; Tammpere, Erik; Kofoed, Megan; Keong, Christelle; Chiang, Jennifer; Giaever, Guri; Nislow, Corey; Hieter, Philip
Abstract: While the pace of discovery of human genetic variants in tumors, patients, and diverse populations has rapidly accelerated, deciphering their functional consequence has become rate-limiting. Using cross-species complementation, model organisms like the budding yeast, Saccharomyces cerevisiae, can be utilized to fill this gap and serve as a platform for testing human genetic variants. To this end, we performed two parallel screens, a one-to-one complementation screen for essential yeast genes implicated in chromosome instability and a pool-to-pool screen that queried all possible essential yeast genes for rescue of lethality by all possible human homologs. Our work identified 65 human cDNAs that can replace the null allele of essential yeast genes, including the nonorthologous pair y RFT1 /h SEC61A1 . We chose four human cDNAs (h LIG1, h SSRP1, h PPP1CA, and h PPP1CC ) for which their yeast gene counterparts function in chromosome stability and assayed in yeast 35 tumor-specific missense mutations for growth defects and sensitivity to DNA-damaging agents. This resulted in a set of human–yeast gene complementation pairs that allow human genetic variants to be readily characterized in yeast, and a prioritized list of somatic mutations that could contribute to chromosome instability in human tumors. These data establish the utility of this cross-species experimental approach.